The Crusader Kingdoms, an Archival Crossroads - Francisco Apellániz (Al-Qantara : Revista de Estudios Arabes, 2024)
The retrieval of an Arabic notary deed produced in Cyprus in 1435 triggers this inquiry into the overlapping scribal systems under the Crusaders. Some actors and institutions, such as the Genoese and Venetian notaries operating on the island, conspired to form archival collections. Yet the article discusses the Crusaders’ reluctant attitudes toward writing and archiving their own laws and the myths around old archives and their destruction that arose in the literature. The practice of Frankish chanceries, populated mainly by Syrians, and that of Arabic scribes and their Islamic-like notarial system did not derive into the formation of archives. These actors, it is argued, followed an archival logic that had much in common with their Islamic counterparts. In light of the Crusader archival paradox, the article reconsiders recent literature dealing with chancery practices, the materiality of documents, and the lack of archives in Medieval Islam.